Influence of hospital policy on partograph use in tertiary care facilities in India: a cross sectional survey - Singh, Shalini; Singh, Vishwajeet; Thakur, Tushita; Radhika, A. G.; Mittal, Pratima; Kashyap, Jyotika A.; Gupta, Abhilasha; Aggarwal, Neelam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Partograph is an effective, but underutilized tool for monitoring labour. This study examined the influence of hospital policy on the knowledge, attitude, practice and skills of doctors towards partograph plotting. Methods: A cross-sectional survey among doctors posted in labour rooms of tertiary care public teaching hospitals of India was carried out, using self-administered questionnaire to assess knowledge, attitude and practice; and labour case scenarios were provided to assess partograph plotting skills. Chi-square test or Fisher’s exact test were employed to test the significance of association between knowledge, attitude, practice and skills of 150 doctors working in hospitals with (n=3) and without (n=2) policy of routine partograph plotting. Results: The majority of doctors in both groups had correct knowledge about different partograph components. However, doctors working in hospitals with a policy of partograph use, demonstrated significantly better skills using case scenarios for plotting partographs (p<0.01), and a positive attitude towards plotting partograph and its use as a decision support tool (p=0.000) as compared to doctors working in hospitals without a routine partograph plotting policy. Conclusions: Hospital policy of routine partograph plotting may positively influence utilization of partograph in tertiary care public hospitals in India.